A Host‐Dependent Prognostic Model for Elderly Patients with Diffuse Large B‐Cell Lymphoma. (13th April 2017) - Miura, Katsuhiro; Konishi, Jun; Miyake, Takaaki; Makita, Masanori; Hojo, Atsuko; Masaki, Yasufumi; Uno, Masatoshi; Ozaki, Jun; Yoshida, Chikamasa; Niiya, Daigo; Kitazume, Koichi; Maeda, Yoshinobu; et al.
Abstract : Background: Decision‐making models for elderly patients with diffuse large B‐cell lymphoma (DLBCL) treated with rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R‐CHOP) are in great demand. Patients and Methods: The Society of Lymphoma Treatment in Japan (SoLT‐J), in collaboration with the West‐Japan Hematology and Oncology Group (West‐JHOG), collected and retrospectively analyzed the clinical records of ≥65‐year‐old patients with DLBCL treated with R‐CHOP from 19 sites across Japan to build an algorithm that can stratify adherence to R‐CHOP. Results: A total of 836 patients with a median age of 74 years (range, 65–96 years) were analyzed. In the SoLT‐J cohort ( n  = 555), age >75 years, serum albumin level <3.7 g/dL, and Charlson Comorbidity Index score ≥3 were independent adverse risk factors and were defined as the Age, Comorbidities, and Albumin (ACA) index. Based on their ACA index score, patients were categorized into "excellent" (0 points), "good" (1 point), "moderate" (2 points), and "poor" (3 points) groups. This grouping effectively discriminated the 3‐year overall survival rates, mean relative total doses (or relative dose intensity) of anthracycline and cyclophosphamide, unanticipated R‐CHOP discontinuance rates, febrile neutropenia rates, and treatment‐related death rates. Additionally, the ACA index showed comparable results for these clinical parameters when it was applied to the West‐JHOG cohort ( n  = 281). Conclusion: The ACA index has the ability to stratify the prognosis, tolerability to cytotoxic drugs, and adherence to treatment of elderly patients with DLBCL treated with R‐CHOP. Abstract : R‐CHOP has improved the clinical outcome of diffuse large B‐cell lymphoma compared with CHOP alone; however, patients with unfavorable prognostic factors have less change of benefitting from such standard treatments. Advanced age is a crucial risk factor for unfavorable prognosis, as is hypoalbuminemia and medical comorbidities. This study measured the effects of these three biomarkers on clinical outcomes and developed a decision‐making treatment model that can serve as a guide for optimal personalized therapy for elderly patients treated with R‐CHOP.